The Medicinal Accomplishment (sman sgrub) practice in the Dudjom Meteoric Iron Razor (gnam lcags spu gri) tradition: Reflections on the ritual and meditative practice at a monastery in Southern Bhutan. - Cantwell, C (Oxford Centre for Buddhist Studies, 2015)
"Medicinal Accomplishment" (sman sgrub) practices for compounding and empowering medicinal pills have received some attention in studies of Tibetan medical traditions, although it is clear that in the contemporary medical context, their religious significance has been toned down. This paper examines an elaborate "Medicinal Accomplishment" ritual and its Buddhist meditative framing, as performed in a religious monastic context in Bhutan. It explores aspects of the practice, especially the transformations of the substances considered to be enacted through the meditative ritual and tantric accomplishment, raising the question of whether an important aspect of Tibetan medicine in the past may have been neglected in the contemporary focus on the active natural ingredients in Tibetan pills.